Effect of Employee Involvement in Decision Making and Organization Productivity - Charles J. , Mambula I; Francis, Felix; Zirra, Clifford Tizhe Oaya (Archives of Business Research, 2021)
The study is to examine the relationship between involvements in decision making and organization productivity. Employee involvement decision making (EIDM) is the extent in which employers allow its employees to involve in organizational decision making. The study was designed to investigate Deposit Money Bank in Yola (Access Bank). The focus of the study was to find out how involvements in decision making were handled in the organization. The simple and purposive sampling techniques were used to obtain a sample of 50 respondents for study, the questionnaire consisting of 20 questions on the various employee involvements in decision making in an organization and the data collected were analysed using tables and percentages. Finding from the study indicated that employee involvement in decision making is an effective tool to enhance productivity. The research revealed that allowing all employees to involve in decision making is the best and help increases commitment of workers as well as promoting creativity and innovation in the organization. The paper recommended that employees should be involved in decision making of an organization because it makes the workers feel part as owner of the organization; the relationship between managers and employee should be encouraged to enhance consultation and free flow of information in an organization.